Pediococcus acidilactici MI129-DERIVED POSTBIOTIC FORMULATIONS: IN VITRO INSIGHTS INTO APPLICATIONS FOR HEALTH IMPROVEMENT - Pristavu, Mircea Cosmin; Diguță, Filofteia Camelia; Badea, Florentina; Aldea, Alexandru Constantin; Copaloni, Anna; Matei, Florentina (AgroLife Scientific Journal, 2025)
The skin microbiome is crucial for maintaining epidermal barrier integrity and immune homeostasis. This study was conducted to assess in vitro the efficacy of postbiotic formulations prepared from the cell-free supernatant (CFS) of Pediococcus acidilactici MI129, formulated as micellar water and dietary supplement capsules. Seven genes associated with bacteriocin biosynthesis (nis, plnN, plnEF, plnS, plnA, plnQ, and plnW) were detected in the MI129 genome. A multiplex PCR method was established and effectively applied to identify key bacteriocin genes (plnQ, plnS, plnEF, plnW). Both postbiotic formulations exhibited notable antimicrobial activity, generating clear zones of inhibition against all pathogenic indicator strains tested, and demonstrated significant antioxidant activity, indicating their potential to enhance cutaneous health. These results suggest that postbiotics from P. acidilactici MI129 may contribute to skin barrier reinforcement and microbial balance, highlighting their applicability along the skin-gut axis. Future in vivo studies are required to validate these findings and explore the dynamics of postbiotic-skin microbiome interactions.
Keywords: Pediococcus acidilactici; multiplex PCR; postbiotic formulations; antimicrobial activity; antioxidant activity